Empowerment of family welfare empowerment groups through the pagupita garbage bank in Tampingan, Magelang Regency - Kurnia, Marlina; Febrian, Armyana Wahyu Nur; Sari, Dewi Paramita; Azalia, Azalia; Sari, Susi Puspa; Damayanti, Ayesha Sekar (Community Empowerment, 2021)
Community awareness and skills education in waste management by applying the principles of reduce, reuse and recycle (3R) is important in solving waste problems. Especially with the existence of a waste bank as social capital in community-based waste management. The activity of a waste bank is a concept of collecting dry waste and sorting it and having management like a bank, but the savings are not in the form of money but garbage. The results of this community service showed that the implementation of community empowerment through the waste bank in Tampingan has activities that include socialization of the waste bank, waste storage, waste selection, skills training and evaluation. Community empowerment through waste banks on environmental aspects has had a positive impact, particularly in relation to environmental cleanliness. As for the economic aspect, it can provide additional income for active members, and on the social aspect, it can further strengthen social relations.